Black carbon and other light‐absorbing particles in snow of central North America. Issue 22 (25th November 2014) - Doherty, Sarah J.; Dang, Cheng; Hegg, Dean A.; Zhang, Rudong; Warren, Stephen G.
Abstract Vertical profiles of light‐absorbing particles in seasonal snow were sampled from 67 North American sites. Over 500 snow samples and 55 soil samples from these sites were optically analyzed for spectrally resolved visible light absorption. The optical measurements were used to estimate black carbon (BC) mixing ratios in snow (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2t287qmp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CBCest</alternatives>), contributions to absorption by BC and non‐BC particles, and the absorption Ångström exponent of particles in snow and local soil. Sites in Canada tended to have the lowest BC mixing ratios (typically ~5–35 ng g−1), with somewhat higher <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2t287qh1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CBCest</alternatives> in the Pacific Northwest (typically ~5–40 ng g−1) and Intramountain Northwest (typically 10–50 ng g−1). The Northern U.S. Plains sites were the dirtiest, with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2t287qps" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CBCest</alternatives> typically ~15–70 ng g−1 and multiple sample layers with >100 ng g−1 BC in snow. Snow water samples were also chemically analyzed for standard anions, selected carbohydrates, and various elements. The chemical and optical data were input to a Positive Matrix Factorization analysis of the sources of particulate light absorption. These were soil, biomass/biofuel burning, and fossil fuel pollution. Comparable analyses have been conducted for the Arctic and North China, providing a broad, internally consistent data set. As in North China, soil is a significant contributor to snow particulate light absorption in the Great Plains. We also examine the concentrations and sources of snow particulate light absorption across a latitudinal transect from the northern U.S. Great Plains to Arctic Canada by combining the current data with our earlier Arctic survey.